2018
DOI: 10.1093/cercor/bhy288
|View full text |Cite
|
Sign up to set email alerts
|

Silent Synapse Unsilencing in Hippocampal CA1 Neurons for Associative Fear Memory Storage

Abstract: Clarifying learning-induced synaptic plasticity in hippocampal circuits is critical for understanding hippocampal mechanisms of memory acquisition and storage. Many in vitro studies have demonstrated learning-associated plasticity at hippocampal synapses. However, as a neural basis of memory encoding, the nature of synaptic plasticity underlying hippocampal neuronal responses to memorized stimulation remains elusive. Using in vivo whole-cell recording in anaesthetized adult rats and mice, we investigated synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Interestingly, the generation of silent synapses has been linked with weakening and elimination of dendritic spines (Graziane et al, 2016)in our case reduced arborization of ventral GCNs. Most notable is that increases in silent synapses play a role in dysregulation of hippocampal storage of fear memories (Wang et al, 2019). In addition to the biochemical changes, histochemical analysis indicated that reduced dendritic arborization and reduced excitability of ventral GCNs were associated with reduced Fos expression in ventral GCNs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the generation of silent synapses has been linked with weakening and elimination of dendritic spines (Graziane et al, 2016)in our case reduced arborization of ventral GCNs. Most notable is that increases in silent synapses play a role in dysregulation of hippocampal storage of fear memories (Wang et al, 2019). In addition to the biochemical changes, histochemical analysis indicated that reduced dendritic arborization and reduced excitability of ventral GCNs were associated with reduced Fos expression in ventral GCNs.…”
Section: Discussionmentioning
confidence: 99%
“…Moving from the whole cell to the single-synapse level feels much like moving into a terra incognita, where many of the molecular events taking place in the active synapse are known, but a comprehensive picture of their relative importance is still missing. Nevertheless, for a set of synapses to form a memory-relevant trace, they should be active during the learning phase-even though silent synapses (Wang et al, 2019) and newly formed synapses may also play a role (Xu et al, 2009;Yang et al, 2009). As we shall see in the next sessions, a number of molecular events that follow synaptic activation have been used to develop reporters to identify active synapses in learning tasks (Figure 1).…”
Section: Tagging Synaptic Engrams: Comparison With Cellular Engramsmentioning
confidence: 99%
“…Hitherto, silent synapses have been implicated in a wide range of neurological diseases, such as neurodevelopmental dysfunctions, addiction, emotional disorders, and traumatic brain injuries etc. ( Callsen-Cencic and Mense, 1999 , Jing et al, 2017 , Lo and Erzurumlu, 2007 , Wang et al, 2019 , Wang et al, 2021a , Wang et al, 2021b , Xia et al, 2017 ), suggesting its universal existence under nonspecific pathological circumstances. Consequently, an intriguing question arises: can silent synapses be generated in the corticospinal motor circuitry by SCI and does their unsilencing contribute to the neuroplasticity potentially harnessed by neuromodulation to strengthen the spared corticospinal synaptic connections after SCI?…”
Section: Introductionmentioning
confidence: 99%